2016
DOI: 10.4049/jimmunol.1501855
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane Phospholipid Binding Protein Annexin A2 Promotes Phagocytosis and Nonlytic Exocytosis of Cryptococcus neoformans and Impacts Survival in Fungal Infection

Abstract: Cryptococcus neoformans (Cn) is a fungal pathogen with a unique intracellular pathogenic strategy that includes non-lytic exocytosis, a phenomenon whereby fungal cells are expunged from macrophages without lysing the host cell. The exact mechanism and specific proteins involved in this process have yet to be completely defined. Using murine macrophages deficient in the membrane phospholipid binding protein, annexin A2 (ANXA2), we observed a significant decrease in both phagocytosis of yeast cells and in the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…Annexin A2 is a calcium responsive phopspholipid binding protein that is associated with diverse cellular processes including pro-inflammatory cytokine release and inflammasome activation in macrophages [55,56]. Deletion of Annexin A2 reduced vomocytosis from mouse macrophages and increased host cell lysis, but how these two effects are related and if macrophage inflammatory cytokines are involved was not determined [57]. The atypical kinase Erk5 was identified in a compound screen to be a negative regulator of vomocytosis [58].…”
Section: The Immune Response and Interaction With Cryptococcimentioning
confidence: 99%
“…Annexin A2 is a calcium responsive phopspholipid binding protein that is associated with diverse cellular processes including pro-inflammatory cytokine release and inflammasome activation in macrophages [55,56]. Deletion of Annexin A2 reduced vomocytosis from mouse macrophages and increased host cell lysis, but how these two effects are related and if macrophage inflammatory cytokines are involved was not determined [57]. The atypical kinase Erk5 was identified in a compound screen to be a negative regulator of vomocytosis [58].…”
Section: The Immune Response and Interaction With Cryptococcimentioning
confidence: 99%
“…Given that there are other receptors on macrophages are crucial for phagocytosis of fungus and CR3 can crosstalk with FcγRIIIB (CD16), 25,26 CD14, TLR2, 27 and dectin-1. 28 Coccidioides posadasii, 29 Aspergillus, 30,31 mycobacteria, 32 Sporothrix schenckii, 33 Cryptococcus neoformans 34 and the strong phagocytosis of T. marneffei by mouse macrophages may stem from the collaboration of multiple receptors. Heinsbroek et al 35 have shown that CR3 can collaborate with dectin-1 and MR for the phagocytosis of C.albicans.…”
Section: Discussionmentioning
confidence: 99%
“…For this to happen, the vesicle itself needs to be positioned near the edge of the cell, and the vesicle and plasma membranes fuse together to allow the cargo to be released. In 2016, Stukes et al showed that annexin A2, a membrane-binding protein involved in bringing membranes together and promoting fusion during several cellular processes including exocytosis of secretory vesicles, affects the occurrence of vomocytosis (Stukes et al, 2016). Using annexin A2 deficient cells (anxa2 -/-), they noticed a decrease in phagocytosis and in vomocytosis of C. neoformans.…”
Section: What Is the Mechanism Of Vomocytosis?mentioning
confidence: 99%
“…In 2016,Stukes et al showed that annexin A2, a membrane-binding protein involved in bringing membranes together and promoting fusion during several cellular processes including exocytosis of secretory vesicles, affects the occurrence of vomocytosis(Stukes et al, 2016). For this to happen, the vesicle itself needs to be positioned near the edge of the cell, and the vesicle and plasma membranes fuse together to allow the cargo to be released.…”
mentioning
confidence: 99%